Fibrous Aerogels for Solar Vapor Generation - Xu, Chengjian; Zhang, Junyan; Shahriari-Khalaji, Mina; Gao, Mengyue; Yu, Xiaoxiao; Ye, Changhuai; Cheng, Yanhua; Zhu, Meifang (Frontiers in Chemistry, 2022)
Solar-driven vapor generation is emerging as an eco-friendly and cost-effective water treatment technology for harvesting solar energy. Aerogels are solid materials with desirable high-performance properties, including low density, low thermal conductivity, and high porosity with a large internal surface, which exhibit outstanding performance in the area of solar vapor generation. Using fibers as building blocks in aerogels could achieve unexpected performance in solar vapor generation due to their entangled fibrous network and high surface area. In this review, based on the fusion of the one-dimensional fibers and three-dimensional porous aerogels, we discuss recent development in fibrous aerogels for solar vapor generation based on building blocks synthesis, photothermal materials selection, pore structures construction and device design. Thermal management and water management of fibrous aerogels are also evaluated to improve evaporation performance. Focusing on materials science and engineering, we overview the key challenges and future research opportunities of fibrous aerogels in both fundamental research and practical application of solar vapor generation technology.